2015
DOI: 10.1589/jpts.27.1795
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between navicular drop and measuring position of maximal plantar flexion torque of the first and second-fifth metatarsophalangeal joints

Abstract: [Purpose] The purpose of this study was to determine the relationship between navicular drop and plantar flexion torque of the first and second-fifth metatarsophalangeal joints. [Subjects] Ten healthy young men participated in this study. [Methods] The Pearson product-moment correlation coefficient was calculated to determine the relationship between navicular drop and plantar flexion torque of the first and second-fifth metatarsophalangeal joints. [Results] Significant negative correlations were observed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…For analysis, the average torque between the two measurements conducted at each position was chosen. The reliability of the measurements was previously reported [14].…”
Section: Measurement Of Mvc Torquementioning
confidence: 74%
See 1 more Smart Citation
“…For analysis, the average torque between the two measurements conducted at each position was chosen. The reliability of the measurements was previously reported [14].…”
Section: Measurement Of Mvc Torquementioning
confidence: 74%
“…Recently, we developed a device that could measure the plantar-exion torque of the rst MTPJ and a unit of the second-fth MTPJs [14]. It is possible to measure the plantar-exion torque of the rst MTPJ and second-fth MTPJs at various MTPJ and ankle positions.…”
Section: Introductionmentioning
confidence: 99%
“…Since the normalized fiber length of the plantar flexion muscles of the lesser toes was longer than that of the hallux, it seems that the velocity of the muscle contraction was also faster for the lesser toes than for the hallux. According to previous studies, the total PCSA of the plantar flexion muscles of the hallux was larger than that of the lesser toes, and it has furthermore been reported that the plantar flexion muscles of the hallux can produce more torque than those of the lesser toes 14 ) . Overall, since the plantar flexion muscles of the hallux muscle are considered suitable for producing larger forces and the contraction velocity is slower, it appears that displacement is greatly controlled by activation of the plantar flexion muscles of the hallux during postural sway.…”
Section: Discussionmentioning
confidence: 89%
“…However, in this study, there were no significant differences in any of the interventions for the right-left direction components of maximal displacement and postural sway velocity. Many toe plantar flexion muscles run on the sagittal plane, and the center of mass is shifted toward the rear by contraction of the toe plantar flexion muscles 14 ) . Therefore, we speculate that the right-left direction postural control during the single leg stance may instead be controlled at the ankle or more proximal joints.…”
Section: Discussionmentioning
confidence: 99%
“…Second, toe flexor muscles are stretched in flatfoot children, so the muscles cannot contract with maximal strength. Muscles contraction strength exhibits a length-tension relationship 25 , 26 , 27 ) , where optimal contraction occurs when the muscle is at the appropriate length and not overly stretched or compressed. In our study, toe grip strength of flatfoot children was lower than that of normal children.…”
Section: Discussionmentioning
confidence: 99%